Literature on the Role of Strategic Planning to Improve the Quality of Education in Nepalese Bachelor-Level Management Educational Institutions - Bhandari, Rohan; Mei, Tan Qing; Adhikari, Basanta Prasad (NPRC Journal of Multidisciplinary Research, 2025)
This literature review investigates the role of strategic planning and its practices in enhancing the quality of education within Nepalese bachelor-level management institutions. Motivated by the observation that top-level administrators often formulate strategic policies for quality improvement but fail to implement them effectively in practice, leading to declining educational quality and student flight to foreign universities, the study evaluates the key findings and gaps from 25 selected articles. The methodology involved a comprehensive literature review, which identified, screened, and analyzed studies related to strategic management practices and educational quality in the Nepalese context. The synthesized findings identify six critical thematic categories: strategic management practices, strategic planning and leadership, quality management systems, stakeholder engagement and governance, sustainability and resource management, and institutional development. The results consistently confirm that strategic planning and quality assurance are essential mechanisms that positively influence curriculum alignment and institutional quality culture. However, the review identifies a persistent and critical gap between policy and execution. The research is methodologically limited by a firm reliance on qualitative and descriptive approaches, which provide rich contextual detail but lack the statistical rigor needed to validate claims of "positive impact" or to establish causal links. Consequently, there is limited empirical evidence connecting strategic plans to measurable outcomes such as graduate employability or student learning achievement. Furthermore, the governance aspect remains underexplored, lacking a unified framework. This study concludes that while advancements in policy are notable, future research should adopt longitudinal and comparative mixed-methods analysis, focusing on quantifiable outcomes, to guide data-driven strategies for sustained quality improvement.